Respostas

2014-01-30T11:37:41-02:00
Chamando x²=y --> Condição de existência y>0
a equação fica da seguinte forma

y²-26y+25=0
delta= b² - 4ac
delta= 676-100
delta=576

y'= (26+24)/2 ---> y'= 25

y"= (26-24)/2 ---> y"=1

x²= 25  ou         x²=1       
x=5 ou x= -5    x=1 ou x= -1 

S:{ -5, -1, 1, 5 }
1 5 1
2014-01-30T11:43:08-02:00
X²=y

y²-26y+25=0
Δ = b² -4ac
Δ = (-26)² -4 *1 * 25
Δ = 676 -100
Δ = 576
y' = (-b + √∆)/ 2a
(-(-26) + 24)/2 * 1
(26 + 24)/2
50/2
25
y'' = (-b - √∆)/ 2a
(-(-26) - 24)/2 * 1
(26 - 24)/2
2/2
1

x
²=y; y'=25 e y'' = 1.

x²=25
x=+-√25
x=+-5

x²=1
x=+-√1
x=+-1

\[\boxed{S={-5,-1,5,1}}\]

1 5 1